2005
DOI: 10.1128/jcm.43.6.2559-2562.2005
|View full text |Cite
|
Sign up to set email alerts
|

Pandemic Serovars (O3:K6 and O4:K68) of Vibrio parahaemolyticus Associated with Diarrhea in Mozambique: Spread of the Pandemic into the African Continent

Abstract: Forty-two episodes of Vibrio parahaemolyticus infections were detected in Beira, Mozambique, from January to May 2004. The majority of the isolates (81%) belonged to the pandemic serovars (O3:K6 and O4:K68) of V. parahaemolyticus. The pandemic serovars were positive by group-specific PCR (GS-PCR) and a PCR specific for open reading frame ORF8 (ORF8-PCR), which are molecular markers of the pandemic clone, and were positive for tdh but negative for trh. The remaining 19% of the strains also possessed the tdh gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
78
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(80 citation statements)
references
References 22 publications
2
78
0
Order By: Relevance
“…The isolate was not susceptible only to ampicillin and susceptible to the remaining 12 antibiotics. These results are consistent with those of previous studies (25,38,39), which indicated that many V. parahaemolyticus isolates were resistant to ampicillin and susceptible to most of the other examined antibiotics.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The isolate was not susceptible only to ampicillin and susceptible to the remaining 12 antibiotics. These results are consistent with those of previous studies (25,38,39), which indicated that many V. parahaemolyticus isolates were resistant to ampicillin and susceptible to most of the other examined antibiotics.…”
Section: Discussionsupporting
confidence: 93%
“…To date, more than 80 different combinations of the O and K serotypes have been identified (22). Since 1996, serotype O3:K6 clones identified in India (23) have been disseminated worldwide, and this pandemic clonal group has been reported in many countries (24)(25)(26)(27). This group includes not only O3:K6 serotype strains but also their serovariants.…”
Section: Introductionmentioning
confidence: 99%
“…Although infections caused by V. parahaemolyticus are usually sporadic cases caused by various serotypes of this organism, strains with O3:K6 and a few other serotypes, such as O4:K68, O1:K25, and O1:K untypeable (O1:KUT), have caused an increasing number of worldwide outbreaks of gastroenteritis since 1996 (1,4,5,6,7,18,19,21,26). These strains showed almost identical fragment patterns of pulsed-field gel electrophoresis (PFGE) and arbitrarily primed PCR and are referred to as "pandemic clones" (2,19,21,26,36).…”
mentioning
confidence: 99%
“…Infections by the virulent strains had been limited to local areas before 1995. However, a new pathogenic type of V. parahaemolyticus emerged in Asia in 1995 and then infection by these new-type strains spread rapidly to North and South America, Europe, and Africa (Okuda et al, 1997;Matsumoto et al, 2000;MartinezUrtaza et al, 2004;Ansaruzzaman et al, 2005;González-Escalona et al, 2005;Cabanillas-Beltrán et al, 2006;Nair et al, 2007). Because the infection by these strains spread across international borders, these strains have been called "pandemic" or "post-1995 pandemic" strains (Matsumoto et al, 2000;Hurley et al, 2006).…”
Section: Introductionmentioning
confidence: 99%